Self-limited self-assembly of nanoparticles into supraparticles: towards supramolecular colloidal materials by design - Piccinini, Esteban (2016)
For quite a while, scientists have resorted to colloidal synthesis to mimic complex structural and functional materials found in Nature. In particular, within the past few years, the synthesis of suprastructures with novel properties that emerge from the coupling of diverse nanoscale functional units has defined new boundaries in materials science. In this mini-review, we survey the most recent and outstanding achievements on the rational design of supraparticles based on the self-limited self-assembly of nanoparticles, and their application in fields like biology, medicine and energy.